BUSINESS SUCCESS THROUGH INTELLECTUAL PROPERTY - Markova, Assoc.Prof. Dr. Maria (IJRDO - Journal of Business Management, 2018)
The aim of this article is to present a new business model for business success based on intellectual property /IP/ capital of the company. The author’s thesis is: IP capital is a tool for company competitiveness and to achieve company competitiveness the company’s management should form a business model based on IP capital. The author presents definitions for the following terms: ‘business success, IP capital, business model. The structure of the article is: Business success – general notes. Intellectual property capital and company competitiveness. Business model conception based on IP capital. Implementation of the business model based on IP capital in Bulgaria First of all the author presents hers point of view for a business success and the matrix for its evaluation including financial indicators and nonfinancial indicators such as purchases, turnover and profit, revenues from IP and profitability. Special attention is paid to IP capital as IP rights - list and structure, expert assessment of their value. Then the author presents the relations between IP capital and company competitiveness through revelation of the aspects: IP as innovations and IP as business indicators and then IP as a market factor and as a factor of competitiveness. The final part of this article is focused on the business model based on IP capital. The author presents his point of view for the business model as a management term. Then, special attention is paid to the business model based on IP capital which includes: Analysis of current status of the business unity as general. Identification of IP capital as elements and characteristics. Forming the company’s strategy for a development based on IP capital The practical issue of the business model is presented as results of the implemented EC operational program for competitiveness of the Bulgarian economy /2007-2016/, protected IP rights within Bulgarian patent office and analysis of the figures and facts.